Family honor - Parker, Robert B. (New York : Berkley Books, 2000)
PI Sunny Randall of Boston searches for a rich man's daughter who ran away to be a prostitute. After finding her Sunny must guard her because the girl is on a hit list. She witnessed a conspiracy involving state government.
Keywords: Women private investigators -- Massachusetts -- Boston -- Fiction; Detective and mystery fiction